Moderating effect of gender in repatronage behavioral intention: the role of personal characteristics - Wong, Yue Teng; Osman, Syuhaily; Mat Said, Aini; Paim, Laily (Canadian Center of Science and Education, 2014)
The agendas of consumer-centric marketing and remarkable revolution of gender in consumption have prolonged the reformation in marketing module as to entice the repatronage shoppers. The focuses of this study were to examine the repatronage behavioral intention from the personal characteristic perspective and to identify the gender-invariant of the causal relationships. Specifically, this study aimed to investigate the relationships between personal characteristics (need for activity, impulsiveness, shopping confidence, interpersonal influence susceptibility, utilitarian and hedonic shopping orientations) and repatronage behavioral intention as well as to assess the moderation effects of gender on the relationships. Reasoned Action Approach was employed as the theoretical basis of the study. The responses from 569 apparel adult shoppers were used for data analysis. Personal characteristics were found significantly associated with the repatronage behavioral intention. There was a moderation effect of gender ascertained in the identified relationships. The present study discerned some important implications for the marketing practitioners to gain insight into the characteristics of their targeted shoppers as to customize and position their product offerings accordingly.